The Topographic Signature of Ecosystem Climate Sensitivity in the Western United States. Issue 24 (23rd December 2019) - Hoylman, Zachary H.; Jencso, Kelsey G.; Hu, Jia; Holden, Zachary A.; Allred, Brady; Dobrowski, Solomon; Robinson, Nathaniel; Martin, Justin T.; Affleck, David; Seielstad, Carl
Abstract: It has been suggested that hillslope topography can produce hydrologic refugia, sites where ecosystem productivity is relatively insensitive to climate variation. However, the ecological impacts and spatial distribution of these sites are poorly resolved across gradients in climate. We quantified the response of ecosystem net primary productivity to changes in the annual climatic water balance for 30 years using pixel‐specific linear regression (30‐m resolution) across the western United States. The standardized slopes of these models represent ecosystem climate sensitivity and provide a means to identify drought‐resistant ecosystems. Productive and resistant ecosystems were most frequent in convergent hillslope positions, especially in semiarid climates. Ecosystems in divergent positions were moderately resistant to climate variability, but less productive relative to convergent positions. This topographic effect was significantly dampened in hygric and xeric climates. In aggregate, spatial patterns of ecosystem sensitivity can be implemented for regional planning to maximize conservation in landscapes more resistant to perturbations. Plain Language Summary: It is well known that gradients in elevation and aspect can have a significant influence on the degree of water and energy available for plant growth and the sensitivity of ecosystems to wet or dry time periods. Little work has examined how hillslope topography and downslope movement of water to zones of convergent terrain can impact plant available water and vegetation growth. We quantified ecosystem response to the climatic water balance (ecosystem sensitivity) across a 30‐year record and at a 30‐m resolution across the western United States. Our results show that vegetation in zones of hillslope convergence, where moisture from upslope tends to accumulate, is less sensitive to droughts, especially in semiarid settings. Divergent hillslope positions were moderately sensitive to climate and less productive relative to convergent positions. Ecosystem response to topography was dampened in especially wet or dry climates due to significant moisture surplus or moisture deficit, respectively. These distributed measurements of ecosystem sensitivity are important considerations when describing local ecosystem‐climate relationships and for identifying management priorities across landscapes. Zones of resistant vegetation are more likely to persist through future droughts, influencing the greater ecosystem's response to climate change. Key Points: Convergence of hillslope topography contributes to higher ecosystem net primary productivity across the majority of the western United States Hillslope convergence reduces ecosystem sensitivity to climate, especially within semiarid regions Ecosystems in flat, arid environments are the most vulnerable to drought‐induced reductions in productivity